Analisis Hukum Bisnis terhadap Normalisasi Pengelolaan Pabrik Minyak Goreng Kelapa Sawit (PAMIGO) Berskala Mikro di Desa Curug Lang Lang Kecamatan Munjul-Pandeglang - Jumhana, Enjum (Journal of Multidisciplinary Inquiry in Science, Technology and Educational Research, 2024)
This research aims to analyze business law aspects related to the normalization of the management of micro-scale Palm Oil Mill (PAMIGO) in Curug Lang Lang Village, Munjul Sub-district, Pandeglang Regency. This micro-scale factory has an important role in the local economy, but faces various legal and regulatory challenges that need to be considered in its management. This research uses a descriptive qualitative approach with a case study method, where data is collected through in-depth interviews, direct observation, and document analysis. The results show that the management of PAMIGO in Curug Lang Lang Village is not fully in accordance with applicable regulations, especially in the aspects of business licensing, environmental protection, and workers' rights. Therefore, normalization efforts are needed through policy adjustments and capacity building of factory managers to comply with applicable legal standards, for operational sustainability and legal compliance. The conclusion of this study emphasizes the important role of local government and other stakeholders in supporting the normalization process, in order to increase PAMIGO's contribution to the local economy while ensuring ongoing legal compliance.